The effect of L-glutamine supplementation on the digestive physiology of Senegalese sole larvae, Solea senegalensis (Kaup, 1858) - Viegas, Ana Rita Gomes (2021)
Senegalese sole (Solea senegalensis) is an altricial species, which undergo dramatic transformations before metamorphosing into juvenile. Therefore, larvae must capture and process exogenous food even though the digestive tract may not be fully developed. The inadequate digestion/absorption of exogenous nutrients resulting from late maturation of the enterocytes at the intestinal epithelium has hampered a successful juvenile production of this promising flatfish species. Glutamine is a conditionally essential FAA which is involved in immune function and intestinal health, and has been widely used in aquaculture. A 22-day feeding trial was conducted to evaluate the effect of dietary L-glutamine supplementation on the growth performance, survival, metamorphosis, and digestive physiology during the early life stage of Senegalese sole. Two experimental diets were established with different levels of L-glutamine enrichments – 0.0 g l-1 (CTL) and 0.5 g l-1 (GLN). Experimental treatments were randomly assigned to triplicate groups stocked at a density of 0.26 individuals cm-2, reduced to 0.14 individuals cm-2 at 19 DAH, in each tank. The results showed that growth performance and enterocyte height of fish fed L-glutaminesupplemented diet were significantly increased compared to the control group (p<0.05). Survival and metamorphosis were not significantly different between dietary groups (p>0.05). Significant improvements were observed on specific activity of pepsin-like and amylase from CTL group, whereas BB aminopeptidase was highlighted in GLN group (p<0.05). Total activity of pepsin-like, amylase and acid phosphatase from CTL group was greater (p<0.05) than GLN group, whereas BB aminopeptidase total activity and IMI assayed through this enzyme showed better results in GLN group. Specific and total activity of trypsin, aminopeptidase, and intestinal and BB alkaline phosphatase did not differ between groups. Also, acid phosphatase specific activity was not affected by dietary L-glutamine. In conclusion, dietary L-glutamine supplementation could improve the growth performance and enterocyte height at the intestinal epithelium of sole post-larvae. Further studies are needed to clarify the effect of L-glutamine supplementation on enzymatic activity.